Botanical trends in global skin care: a bibliometric analysis - Sri Kuncari, Emma; Purnomo, Purnomo; Ritmaleni, Ritmaleni; Sujarwo, Wawan (Ethnobotany Research and Applications, 2025)
Background: The trend of using botanical-based ingredients in skin care is booming in the global cosmetics industry. A comprehensive and global bibliometric analysis of this field has never been conducted. This study aims to conduct a bibliometric analysis of the current literature from 2000 to 2024 on the use of botanical ingredients in skin care. This analysis aims to identify global and comprehensive research trends and develop future research strategies. Methods: References were obtained from the Scopus database. The data mining process involved filtering, extraction, export, selection, and validation. A data cleaning process was conducted to standardize the writing. The data were then analyzed and visualized using Bibliometrix-Biblioshiny, VOSviewer, and Microsoft Excel. Results: The use of botanical ingredients in global skin care is on the rise. Between 2000 and 2024, 1,127 articles were published by 357 publishers, with a 12.3% average annual growth. A total of 4,942 authors from 77 countries contributed to this topic. The United States is the leading contributing country, Tsinghua University is the most productive institution, Science of the Total Environment is the top journal, and Gang Yu is the most prolific author. The U.S. plays a key role in knowledge dissemination on this subject. Conclusions: The bibliometric analysis reveals growing interest and underscores opportunities for international collaboration, offering a useful reference for academics, researchers, and policymakers to bridge scientific and technological gaps and inform future policies and research. Keywords: Bibliometric, Botanical, Science mapping, Skin care